Sexual stigmas among lesbian, gay, and bisexual individuals with problematic internet use and depression - Wang, Peng-Wei; Chang, Yu-Ping; Tsai, Ching-Shu; Yen, Cheng-Fang (Frontiers in Psychiatry, 2023)
Sexual stigma causes psychological distress among lesbian, gay, and bisexual (LGB) individuals. LGB individuals are more likely to exhibit both problematic Internet use (PIU) and significant depression than are heterosexual individuals. Whether the severities of sexual stigma varied among LGB individuals with various statuses of comorbid PIU and depression warrants study. The present study aimed to investigate the differences in the experiences of familial sexual stigma (FSS), internalized sexual stigma (ISS), and sexual orientation microaggressions (SOMs) among LGB individuals with various statuses of comorbid PIU and depression. In total, 1000 self-identified LGB young adult individuals participated in the study. The level of PIU was assessed using the Chen Internet Addiction Scale, depression was assessed using the Center for Epidemiological Studies-Depression Scale, the experience of FSS was assessed using the Homosexuality-Related Stigma Scale, the experience of ISS was assessed using the Measure of Internalized Sexual Stigma for Lesbians and Gay Men, and the experience of sexual orientation microaggression was assessed using the Sexual Orientation Microaggression Inventory. The differences in the levels of FSS, ISS, and SOMs among the four groups (i.e., the groups with both PIU and depression [comorbid group], only depression, only PIU, and neither PIU nor depression [neither group]) were investigated using multivariate analysis of covariance. The results indicated that LGB individuals with comorbid PIU and depression reported higher levels of ISS and SOMs than did those with depression only and PIU only, respectively. Moreover, LGB individuals with PIU or significant depression had higher levels of FSS and SOMs than did those with neither PIU nor depression. The results of this study supported that the experiences of FSS, ISS, and SOMs were significantly associated with various levels of PIU and depression in LGB individuals.